The hope we seek : : a novel - Shapero, Rich (Outside Reading, 2014)
Zachary Knox, a sharpshooter known as "the Bull's-Eye Telepath," heads north in search of gold. On his way he meets Sephy, a magnetic woman on the trail of her lost brother. But on arrival, they find the mining camp is home to a shadowy mining company. The mine boss, Trevillian, rules the camp like a despotic priest, and at the center of his faith is Hope, an elusive goddess for whom the miners toil, enduring increasingly perilous trials as they pursue her into the depths of the earth. Zack determines to overthrow Trevillian, guided by Sephy's cryptic directions, until Hope appears and reveals the astonishing future she has in mind for him. The Hope We Seek transports us to a netherworld of danger and allure, where arduous labor, sustained by unwavering belief, promises an unearthly reward. Shapero holds a dark mirror to the passions that drive us, and the extremes to which we go to find meaning in our lives